Social Variation of Language Users - Fadila Oktaviana (Journal of English Language Teaching and Cultural Studies, 2018)
This study aimed to describe the social variation of language based on level of education, type of work, and a social institution on Facebook users with the age range of 20-50 years. The source of the data in this study was status written on social media in this case Facebook. The data collecting technique was content analysis. The results of the analysis indicated that the educational background, the type of work which is owned as well as social institution belonging to the users of the language are very influential in content writing, word choice and writing text in communication. Although, those are not only the usually factors because there were others influenced factors such as psychology, writing style, and others.